Who is who in fact-checked conspiracy theories? Disseminators, sources, and the struggle for authority in polarized environments - Marques, Francisco Paulo Jamil; Ferracioli, Paulo [UNESP]; Comel, Naiza; Kniess, Andressa Butture (SAGE Publications, 2023)
Despite the growing scholarship concerning mis- and disinformation, research has yet to assess how journalism tackles conspiracy theories in settings where news organizations and media professionals have their authority questioned. Against this background, our article poses two research questions: RQ1) Who are the actors mainstream fact-checkers cover when addressing conspiracy theories? RQ2) To what extent does the focus on such actors delegitimize those who challenge news organizations or compete with them for the audience? Using content analysis as our key methodological strategy, we consider 197 fact-checks published between 2018 and 2021 by the Projeto Comprova, a Brazilian initiative currently comprising professionals from 41 media organizations. We found that the most discussed topics were those mobilizing polarized groups, namely, the Covid-19 pandemic and election fraud allegations. The then-President Bolsonaro and his supporters were often cited as disseminators of such plots. In turn, Facebook is pointed out as a thriving environment for the circulation of conspiratorial narratives. The results also reveal the prominence of mainstream news outlets as sources to ground the “factual” information sustained in the fact-checks. More interestingly, our data suggest that fact-checkers have favored specific news values when addressing conspiracy theories. To strengthen our investigation, we use interviews with four professionals contributing to the Comprova to illustrate how the project has brought together rival companies interested in delegitimizing “alternative” sources of information.
Keywords: Conspiracy theories; content analysis; disinformation; fact-checking; global south; journalism; polarization; social media